Pelatihan keterampilan sosial pada mahasiswa yang sulit bergaul = Social skills training on shy-socially isolated students - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Social skills training is a technique in behavior modification which is usually used to increase social skills of subjects who have psycholop. cal handicap. The purpose of this study is to find out whether social skills training is effective in increasing social skills on shy-socially isolated subjects. This study is also intended to find out whether social anxiety and self-concept are also affected by this technique. Nineteen students participated in this study. They were selected based on their scores on social behavior scale (STLS). Subject who had scores less than 98 or in category of lower normal were selected for this study. They were placed into two groups, 10 in the experimental group and 10 in the control group. Training was conducted by two trainers (male and female) who had sufficient training in group discussion and therapy. Treatment group met twice a week for 90-120 minutes in six weeks. Evaluation on treatment effectiveness was measured three times, during pre-treatment, post-treatment, and follow-up three months after treatment had been conducted. Measures used were three self-reports on social behavior, social anxiety, and self-concept. Experimental subjects were also given evaluation form for treatment procedures. Results of this study showed that social skills training was effective in increasing social skills. Subjects who were in the experimental group showed significant increase in social behavior and self-concept than control group. They also showed significant decrease in social anxiety than control group.